Die DFU zeigt Chile : Dokumentarfilm (Deutsche Friedensunion, 1977)
Green-tinted portrait of Augusto Pinochet; collage of photographs and cuttings in the background Poster advertising documentary 'Die DFU zeigt Chile' PO-1548